Proffering absurd candidate formulations in the pursuit of progressivity. Issue 3 (3rd July 2022) - Amar, Cheikhna; Nanbu, Zachary; Greer, Tim
ABSTRACT: Based on interaction recorded in EFL classrooms, this study uses Conversation Analysis to document the post-first deployment of an absurd candidate formulation (ACF) to pursue recipient response at points of interactional delay. ACFs are a form of correction-invitation device in which the question initiator proffers a candidate response that is hearably inappropriate/inaccurate and therefore designed to be rejected by its recipient and replaced with a more plausible response. The design of the ACF turn is extreme, hyperbolic, absurd or otherwise implausible in nature, and the participants treat it as such via laughter and next-turn negation. ACFs thus help recipients arrive at an acceptable answer by eliminating obviously inappropriate alternatives and indexing a particular class of response. When used in conjunction with more plausible alternatives, ACFs can guide the recipient to select one of those candidates. Even so, recipients can resist the question by providing only minimal responses. Our data are taken from video-recordings of naturally occurring classroom interaction between L1-speaking EFL teachers and L2 learners of English.